2020
DOI: 10.1097/j.jcrs.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated corneal crosslinking in children with keratoconus: 5-year results and comparison of 2 protocols

Abstract: Purpose: To evaluate long-term clinical results of 2 different accelerated corneal crosslinking (CXL) protocols in pediatric patients with keratoconus. Setting: Beyoğlu Eye Training and Research Hospital, Istanbul, Turkey. Design: Retrospective case-control study. Methods: Patients who were younger than 18 years were included in the study. Group 1 received 4 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Successful treatments of KC should address two distinct factors: the optical ine ciency of corneal irregularity and the disease progression of corneal bulging; these may be required for corneal transplantation [10]. Recently, CXL performed with the Avedro KXL system has been established as an effective therapeutic technique for halting the progression of KC [2,[4][5][6]. To our knowledge, this study is the rst to retrospectively evaluate the regional corneal epithelial and stromal remodelling after epi-off continuous accelerated CXL with AS-OCT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Successful treatments of KC should address two distinct factors: the optical ine ciency of corneal irregularity and the disease progression of corneal bulging; these may be required for corneal transplantation [10]. Recently, CXL performed with the Avedro KXL system has been established as an effective therapeutic technique for halting the progression of KC [2,[4][5][6]. To our knowledge, this study is the rst to retrospectively evaluate the regional corneal epithelial and stromal remodelling after epi-off continuous accelerated CXL with AS-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…In current study, UDVA signi cantly improved at 3 months after treatment, and UDVA improved or remained stable in 17 (51.5%) eyes at 12 months after treatment with a mean improvement of 0.16 logMAR. A reduction in the keratometric values may be used to assess the e cacy of the procedure [6]. Ağca et al [6] reported the mean reductions in mean K (K mean ) and maximum K (K max ) were less than 0.25 D, and K max decreased ≥ 1.00 D in 38 (33.6%) eyes during the 5 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations